The commercial attractiveness of men's handball in the leading countries of the world - Pavliuk, Iryna (My University, 2022)
The democratization of the Olympic movement, the admission of professional athletes to the Olympic Games contributed to the modification of modern Olympic sports, the system of its management and training of athletes. The popularity of professional sports is growing every year, this is due to objective reasons and, first of all, the intensification of the processes of commercialization and professionalization of elite sports, the increase in the profits of professional sports clubs and athletes, the emergence of new sources of funding, the decisions of the International Olympic Committee (IOC) regarding the admission of professional athletes in certain sports to participate in the Olympic Games. Демократизація олімпійського руху, допуск професійних спортсменів на Олімпійські ігри сприяли модифікації сучасного олімпійського виду спорту, системи його управління і підготовки спортсменів. Популярність професійного спорту зростає з кожним роком, це пов'язано з об'єктивними причинами і, в першу чергу, активізацією процесів комерціалізації та професіоналізації елітних видів спорту, збільшенням прибутку професійних спортивних клубів і спортсменів, появою нових джерел фінансування, рішеннями Міжнародного олімпійського комітету (МОК) щодо допуску професійних спортсменів з певних видів спорту до участі в Олімпійських іграх.
Keywords: гандбол; комерційна привабливість; handball; the commercial attractiveness; кафедра фізичного виховання